Evaluasi Penjadwalan Waktu Pada Proyek Pembangunan Rumah Tipe 30 Di Istana Tegal Besar Kabupaten Jember Dengan Metode CPM - Firdaus Hidayatul Iman; Hadi Wahyono; Eka Bambang Gusminto (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This research was conducted to evaluate the scheduling of time in the project of building type 30 house in Tegal Besar Jember Palace. This research is an action research research using CPM method. The data used in this research are primary data and secondary data. Primary data in this research is data about how long building type 30 housing and expenses incurred to build type 30 house in Tegal Besar Palace Jember. Based on the result of research known that building of type 30 house in Tegal Besar Jember Palace based on CPM method for 54 days. While the cost out to build a type 30 house based on the critical path CPM method of Rp 43.983403. In terms of cost, the completion of the projects is no different because PT. Kinansyah Adi Jaya Land uses wholesale system and housing type 30 subsidized by government.Keywords: Time, Critical Path, Critical Path Method (CPM)